PENGENDALIAN Saprolegnia sp. PADA IKAN NILA (Oreochromis niloticus) DENGAN SALINITAS AIR YANG BERBEDA - Dayu Kurniawan; Dwi Suryanto; Riri Ezraneti (AQUACOASTMARINE, 2015)
DAYU KURNIAWAN. Control of Saprolegnia sp. in Tilapia (Oreochromis niloticus) withDifferent Water Salinity. Under academic supervision By SURYANTO DWI and RIRIEZRANETI.Water quality in fish culture is one of the most important factor that have to bemaintained. Unproper maintained of water quality may result on increase of diseaseprevalence to the fish. One of the disease affected tilapia culture is saprolegniasis caused bySaprolegnia sp.. This study aimed to determine the growth of the fungus Saprolegnia sp. in tilapia(Oreochromis niloticus) in different water salinity as well as to determine the optimum salinity levelsto inhibit the Saprolegnia sp. growth. The growth rate, feed efficiency, survival, fungal colonies,temperature, pH, and DO was measured. The study was conducted with 3 replications and 4treatments, ie 0 ppt, 5 ppt, 10 ppt, and 15 ppt.. The result showed that growth rate were from 0,7 –2,9%, feed efficiency ranged from 30,99 – 61,05%, the survival rate ranged from 6,67 – 90 %and fungal colonies decreased to range between 2,33 – 8,67. Temperatures ranged from 24,9– 26,1°C, pH ranged from 8,3 – 9,0, DO ranged from 6,5 – 7,0 mg/l. Optimum salinity todecrease Saprolegnia sp. in 15 ppt.Keywords: tilapia fish, Saprolegnia sp., Saprolegniasis, Salinity